Dynamics of a Novel Highly Repetitive CACTA Family in Common Bean (Phaseolus vulgaris). Issue 7 (1st July 2016) - Gao, Dongying; Zhao, Dongyan; Abernathy, Brian; Iwata-Otsubo, Aiko; Herrera-Estrella, Alfredo; Jiang, Ning; Jackson, Scott A
Abstract: Transposons are ubiquitous genomic components that play pivotal roles in plant gene and genome evolution. We analyzed two genome sequences of common bean ( Phaseolus vulgaris ) and identified a new CACTA transposon family named pvCACTA1. The family is extremely abundant, as more than 12, 000 pvCACTA1 elements were found. To our knowledge, this is the most abundant CACTA family reported thus far. The computational and fluorescence in situ hybridization (FISH) analyses indicated that the pvCACTA1 elements were concentrated in terminal regions of chromosomes and frequently generated AT-rich 3 bp target site duplications (TSD, WWW, W is A or T). Comparative analysis of the common bean genomes from two domesticated genetic pools revealed that new insertions or excisions of pvCACTA1 elements occurred after the divergence of the two common beans, and some of the polymorphic elements likely resulted in variation in gene sequences. pvCACTA1 elements were detected in related species but not outside the Phaseolus genus. We calculated the molecular evolutionary rate of pvCACTA1 transposons using orthologous elements that indicated that most transposition events likely occurred before the divergence of the two gene pools. These results reveal unique features and evolution of this new transposon family in the common bean genome.